Women Literacy and Economic Development - Dr. Namita Verma (International Journal on Economics, Finance and Sustainable Development, 2022)
Role of education and particularly female education in the development process is well documented. Economists of the classical period have also highlighted this association. Besides the social and economic benefits of education, female literacy is considered a bet in improving the health and basic child care. Higher literacy rates show lower poverty ratios in different parts of the world. India has also shown a tremendous increase in its literacy rates since independence, but it too has the largest concentration of poor people in the world. This has been postulated to be tested through the case of India. The socioeconomic impact of female education constitutes a significant area of research within international development. Increases in the amount of female education in regions tends to correlate with high levels of development. Some of the effects are related to economic development. Women's education increases the income of women and leads to growth in GDP. Other effects are related to social development. Educating girls leads to a number of social benefits, including many related to women's empowerment. The belief that women's literacy is the key to development has informed government and international aid agency policy and programmes around the world. In the poorest countries, the gap between male and female literacy rates has led policy makers to focus on increasing women's as opposed to men's access to literacy, through programmes designed particularly around women's reproductive role. Researchers have been concerned to find statistical evidence that there are the positive connections between female literacy rates and health indicators such as decreased child mortality and fertility rates.